Pengaruh Paduan Arang Aktif Kayu Belian/ulin Dan Katalisator Kerang Ale-Ale Pada Proses Pack Carburizing Terhadap Perubahan Komposisi Dan Nilai Kekerasan Baja Karbon Rendah (Low Carbon steel) St 37 - Dwi Handoko; Vivaldi Vivaldi (Politeknik Negeri Pontianak, 2020)
To increase the hardness and wear resistance of low carbon steels (low carbon steel), it is usually done by a hardening process, namely by adding carbon elements. One of these processes is by using the Pack carburizing method. In this study, the pack carburizing process will be carried out on low carbon steel St 37 using activated charcoal media from ironwood combined with ale-ale shells catalyst with a composition of 10%, 20%, 30% 40% and 50%. Furthermore, composition testing and hardness testing were carried out using the Vickers method. The results of this study in the composition test, there was an addition of carbon due to diffusion and an increase in the maximum hardness of the catalyst composition by 30% with a hardness of 572.6 VHN.